2022
DOI: 10.1039/d1tc05782k
|View full text |Cite
|
Sign up to set email alerts
|

Self-carbonization synthesis of highly-bright red/near-infrared carbon dots by solvent-free method

Abstract: Red/near-infrared fluorescent carbon dots (R-CDs) are attracting more attention in biosensing and biophotonics. However, the synthesis and purification of R-CDs are cumbersome, limiting the large-scale industrial production and application. In...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 50 publications
(46 reference statements)
1
21
0
Order By: Relevance
“…90 Recently, the solid-state reaction has been used for the production of high-quality red C-dots. [136][137][138][139][140] Liu et al reported the red/NIR emissive C-dots prepared via a solvent-free carbonization approach with a QY of 57%. 136 Zhang et al proposed a solvent-free solid-state method for red C-dot (R-CD) synthesis by utilizing the dehydration self-carbonation effect of the HSO 3 group in 3,4-diaminobenzenesulfonic acid.…”
Section: Aromatic Compound-based Precursorsmentioning
confidence: 99%
See 2 more Smart Citations
“…90 Recently, the solid-state reaction has been used for the production of high-quality red C-dots. [136][137][138][139][140] Liu et al reported the red/NIR emissive C-dots prepared via a solvent-free carbonization approach with a QY of 57%. 136 Zhang et al proposed a solvent-free solid-state method for red C-dot (R-CD) synthesis by utilizing the dehydration self-carbonation effect of the HSO 3 group in 3,4-diaminobenzenesulfonic acid.…”
Section: Aromatic Compound-based Precursorsmentioning
confidence: 99%
“…136 Zhang et al proposed a solvent-free solid-state method for red C-dot (R-CD) synthesis by utilizing the dehydration self-carbonation effect of the HSO 3 group in 3,4-diaminobenzenesulfonic acid. 137 The assynthesized R-CDs exhibit a QY of 59% and an emission wavelength in the range of 600-800 nm. Niu et al synthesized red emissive C-dots using phloroglucinol and boric acid as precursors by a solid-state reaction with a yield of up to 75%.…”
Section: Aromatic Compound-based Precursorsmentioning
confidence: 99%
See 1 more Smart Citation
“…S3, ESI †), where the characteristic absorption bands at 3434, 1579, 1228 and 1120 cm À1 correspond to the groups of NH/OH, CQN/CQC, C-N, and C-O, respectively. 35,36 In addition, the results of XPS analyses and data of FT-IR indicate that there are abundant chemical groups on the surface of the NCDs.…”
Section: Characterization and Fluorescence Properties Of Ncdsmentioning
confidence: 99%
“…1(b) shows a wide peak centered at 221, corresponding to the (002) plane of graphene. 38 The Raman spectra display two characteristic peaks at 1361 cm À1 and 1588 cm À1 , representing D-band (sp 3 C) and G-band (sp 2 C), respectively (Fig. S4, ESI †).…”
Section: Njc Papermentioning
confidence: 99%